Versatile Cobalt-Catalyzed Enantioselective Entry to Boryl-Functionalized All-Carbon Quaternary Stereogenic Centers - Wang, Chao; Ge, Shaozhong (Journal of the American Chemical Society, 2018)
We report an asymmetric synthesis of chiral boryl-functionalized γ-lactams containing all-carbon quaternary stereocenters via a Co-catalyzed enantioselective hydroboration/cyclization of amide-tethered 1,6-enynes. These enantio-enriched γ-lactam products can be readily converted to a variety of cyclic and acyclic other chiral γ-lactams, pyrrolidin-2,3-diones, β-amino acid N-carboxyanhydrides, and β-amino carboxylic amides.